2012
DOI: 10.1242/jeb.065565
|View full text |Cite
|
Sign up to set email alerts
|

Illumination preference, illumination constancy and colour discrimination by bumblebees in an environment with patchy light

Abstract: SUMMARYPatchy illumination presents foraging animals with a challenge, as the targets being sought may appear to vary in colour depending on the illumination, compromising target identification. We sought to explore how the bumblebee Bombus terrestris copes with tasks involving flower colour discrimination under patchy illumination. Light patches varied between unobscured daylight and leaf-shade, as a bee might encounter in and around woodland. Using a flight arena and coloured filters, as well as one or two d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 25 publications
0
26
0
Order By: Relevance
“…Since different types of illumination can affect bee vision (Arnold and Chittka, 2012) conducting experiments across a variety of lighting regimes may be important. However, brightness has generally been found to be an unimportant variable when chromatic differences provide for discrimination.…”
Section: Discussionmentioning
confidence: 99%
“…Since different types of illumination can affect bee vision (Arnold and Chittka, 2012) conducting experiments across a variety of lighting regimes may be important. However, brightness has generally been found to be an unimportant variable when chromatic differences provide for discrimination.…”
Section: Discussionmentioning
confidence: 99%
“…However, considering the high degree of variability that can be found in natural forest lights because of filtering effects (36), there will likely be cases, such as forest shade and open gaps environments, where any model will likely fail. This failure would explain behavioral observations that individual bumblebees show a tendency to prefer foraging within a constant illumination condition when finding colored flowers (20). How Would Such a System Operate?…”
Section: Significancementioning
confidence: 99%
“…Color signals captured in the bees' photoreceptors are sequentially processed along multiple neural pathways, including opponent neurons in the inner layer of the medulla, which seem to exhibit a capacity to adapt to stimulus input (19). Bumble bees are capable of sensing changes in overhead illumination and making complex foraging decisions (20)(21)(22), suggesting potential use of contextual information for perceiving variations in ambient illumination. For example, considering changes in the illumination from short to long wavelength-rich radiation, free flying bumblebees (23) and honey bees (17, 24) make reliable color decisions for most dynamic changing conditions.…”
mentioning
confidence: 99%
“…In montane systems, dipteran pollinators commonly increase in dominance with increasing elevation while hymenopterans increase with decreasing elevation (reviewed in Hodkinson 2005). Arnold and Chittka (2012) showed that bees displayed greater color discrimination in well-lit environments relative to shaded ones. Second, pollinator preference can change along an altitudinal gradient, irrespective of community composition.…”
Section: Introductionmentioning
confidence: 99%